THE EFFECT OF COLLECTIVISM DIVERSITY TOWARDS MULTICULTURAL TEAMWORK PERFORMANCE AMONG RESTAURANT EMPLOYEES - Zahidah Ab Latif (Universitas Ahmad Dahlan, 2020)
Diversity is now an important factor that impacted workforce performance. Currently, as having a diverse workforce, Malaysia is depending heavily on foreign workers in the hospitality industry. This study examined a conceptual model investigating the effect of diversity particularly collectivism in influencing multicultural teamwork performance. A self-administered questionnaire was conducted in casual ethnic restaurants in Klang Valley, Malaysia. The findings disclosed that collectivism diversity had a significant influence on multicultural teamwork performance. This study is the first to assess cultural value diversity particularly collectivism value on teamwork performance. This study verified that cultural value diversity increases multicultural teamwork performance in the restaurant context in relation to collectivism. The significant results deepen our understandings of the detailed relationships among the variables. In addition, by providing the current phenomena in workforce industry, this study provides insights to the restaurant managers in handling diversity among multicultural employees.